Does the hydrodynamic, morphometric and sedimentary environment explain the structure of soft-bottom benthic assemblages in the Eastern Bay of Seine (English Channel)?. (5th April 2017) - Dauvin, Jean-Claude; Lucas, Sabrina; Navon, Maxime; Lesourd, Sandric; Mear, Yann; Poizot, Emmanuel; Alizier, Sandrine
Abstract: It has been traditionally assumed that the distribution of the macrofauna is mainly related to the nature of the sediment and that the grain size plays a key role. Therefore in some cases such as in the coastal environment submitted to input of fine particles coming from land via estuary, the sediment is not the major factor explaining the spatial distribution of benthic species, assemblages and communities. In fact, sediment samples may not be representative of real life conditions of benthic organisms which are exposed to natural environment and three-dimensional structure of habitat and heterogeneity of sediments with several grain size classes. Based on data acquired in September 2008 and 2009 from the benthic sampling surveys in the eastern part of the Bay of Seine which is characterized by the dominance of heterometric sediment, the main aim of this paper is to study for the first time the existing link between the spatial distribution of the benthic species and assemblages and selected environmental variables such as sedimentary, hydrodynamic and morphometric data, to explain the real part of each abiotic factors in the spatio-temporal structuration of the benthic assemblages in this area at the mouth of the Seine estuary. Redundancy Analyses had permitted to distinguish six assemblages in relation to heterometry of the sediment; current speed, bathymetry and salinity. Generalized Linear Models permitted to explain between 30 and 89% of the variance within the chosen environmental factors. The species with a large distribution at the eastern part of the Bay of Seine were those showing the lowest percentage of explained variance while the species which were located in few stations were those showing the highest percentage of explained variance. Highlights: Sediments of the eastern part of the Bay of Seine are mainly poorly sorted. Six macrobenthic assemblages are distinguished using Redundancy Analysis. Current velocity, bathymetry and salinity are the most important environmental factors. Generalized Linear Models explain 30–89% of the species distribution linked to environmental factors.